Analisis Komparatif: Keabsahan Kesaksian Seseorang Melalui CCTV dalam Pembuktian Kasus Perzinahan Menurut Fikih As-Syafi'i dan Fikih Az-Zhahiri - Mauliza, Siti; Mahmud, Muhammad (Faculty of Law, Andalas University, 2024)
This study aims to analyze the validity of testimonies through CCTV in adultery cases according to As-Syafi'i and Az-Zhahiri jurisprudence. The research employs a comparative analysis method, examining primary sources from both schools of thought. The study investigates the fundamental requirements for witness testimony in adultery cases and how these requirements apply to CCTV evidence. The research findings reveal a significant divergence between the two jurisprudential perspectives. As-Syafi'i jurisprudence strictly requires direct eyewitness testimony, thus rejecting CCTV evidence as valid testimony in adultery cases. Conversely, Az-Zhahiri jurisprudence adopts a more flexible approach, potentially accepting CCTV evidence under specific conditions based on their acceptance of blind witnesses' testimonies. This study concludes that while As-Syafi'i jurisprudence maintains a conservative stance on admissible evidence in adultery cases, Az-Zhahiri jurisprudence demonstrates greater adaptability to technological advancements in evidence gathering. These findings have significant implications for applying Islamic law in contemporary contexts, particularly regarding the use of modern technology in legal proceedings.